A COMPARATIVE STUDY OF EXTROVERTED AND INTROVERTED STUDENTS’ SPEAKING ACHIEVEMENT AT ENGLISH DEPARTMENT OF HALU OLEO UNIVERSITY - Nurzani, Nurzani (Universitas Halu Oleo, 2019)
This study aimed to investigate whether there was a significant difference between extroverted and introverted students in terms of speaking achievement at speaking I class of English Education Department in Halu Oleo University academic year 2016/2017. The design of this study was quantitative comparative study. The population of this study was the entire speaking I class in English Department of Halu Oleo University in academic year 2016/2017 which consisted of two classes in total of 112 students. The sample of this study was chosen randomly of all the population by using Questionnaire of Eysenk Personality Inventory. The instruments of the study were questionnaire and final score of speaking 1 subject. In analyzing the data of the study, the researcher used Independent sample T-test in SPSS 16.0 for windows. In this study, the Independent Sample T-test was showed the value of Sig.(2-tailed) = 0.502 with α = 0.05, H0 was accepted and H1 was rejected. It is because of sig. (2-tailed) value is higher than α value. The result of this study showed that there was no significant difference between extroverted and introverted students’ speaking achievement at speaking I class of English Education Department in Halu Oleo University academic year 2016/2017. This study showed that the students’ personality, either extroverted or introverted did not give significant difference on the achievement of their speaking Keywords: Extroversion, Introversion, and Speaking Achievement